Persepsi Karyawan terhadap Karyawan Disabilitas di Transmart Padang - Wahdini Wahdini; Mega Iswari (Jurnal Penelitian Pendidikan Khusus, 2020)
This research was conduced based on the situation that occurred on Transmart Padang, where a number of people with disability work together with the other normal employees. Employees who have some problem with hearing absolutely have a problem with communication and to do their duty and responsibilities, but the employees with disabilities still try to do their job well. This study uses descriptive qualitative techniques, data collection techniques used are observation, interviews, questionnaires, and documentation studies. This Research subjects were the employees who work at Transmart Padang, who have a relationship with disability employees in distibution of tasks or divisions. The results of this study reveal the fact that employees could not feel something wrong or feeling normal when they do first meet the employees with disabilities, employees with disabilities can also do their work which were their responsibility and can also help the other employee who need it. The weaknesses of employees with disabilities were in communication that was require different efforts compared to other normal employees, but these weaknesses did not become a significant complaint in work process of each employee in Transmart Padang.